2023
DOI: 10.1108/jebde-07-2022-0016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the determinants of continuous intention in TikTok from the perspective of social influence: a mixed approach of SEM and fsQCA

Abstract: PurposeThis study embraces the call for exploring the determinants of continuous intention in TikTok. Taking the perspective of social influence, this study not only tries to explore the contextual sources of two types of social influence but also aims to unveil the influence mechanism of how social influence affects TikTok viewers’ continuous intention.Design/methodology/approachThis study empirically analyzes how TikToker attractiveness, co-viewer participation, platform reputation and content appeal affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…will have greater opportunities to distribute their content and prove their effectiveness. This dynamic typology affords users a more intuitive comprehension of the video influencers' personalities and styles, increasing their effectiveness and further enticing users' willingness to engage with them (Jia et al, 2023). Despite the platform being primarily dedicated to hedonistic distribution, informative videos are becoming increasingly popular.…”
Section: Entertaining Versus Informative Contentmentioning
confidence: 99%
“…will have greater opportunities to distribute their content and prove their effectiveness. This dynamic typology affords users a more intuitive comprehension of the video influencers' personalities and styles, increasing their effectiveness and further enticing users' willingness to engage with them (Jia et al, 2023). Despite the platform being primarily dedicated to hedonistic distribution, informative videos are becoming increasingly popular.…”
Section: Entertaining Versus Informative Contentmentioning
confidence: 99%
“…Social groups are usually people who are essential to respondents and consist of peers, colleagues, and supervisors in the workplace 12 , 41 . Previous studies have shown that the stronger the influence of these groups of people on the respondents, the greater the respondents' intention to perform the behaviour of interest 42 . In other words, reactions and feedback from people who are important to users will influence users' intention to use or not use the innovation.…”
Section: Literature Reviewmentioning
confidence: 99%